Angiogenic, neurotrophic, and inflammatory system SNPs moderate the association between birth weight and ADHD symptom severity. Issue 8 (25th October 2014) - Smith, Taylor F.; Anastopoulos, Arthur D.; Garrett﻿, Melanie E.; Arias‐Vasquez, Alejandro; Franke, Barbara; Oades, Robert D.; Sonuga‐Barke, Edmund; Asherson, Philip; Gill, Michael; Buitelaar, Jan K.; Sergeant, Joseph A.; Kollins, Scott H.; et al.
<x xml:space="preserve">Abstract</x> Low birth weight is associated with increased risk for Attention‐Deficit/Hyperactivity Disorder (ADHD); however, the etiological underpinnings of this relationship remain unclear. This study investigated if genetic variants in angiogenic, dopaminergic, neurotrophic, kynurenine, and cytokine‐related biological pathways moderate the relationship between birth weight and ADHD symptom severity. A total of 398 youth from two multi‐site, family‐based studies of ADHD were included in the analysis. The sample consisted of 360 ADHD probands, 21 affected siblings, and 17 unaffected siblings. A set of 164 SNPs from 31 candidate genes, representing five biological pathways, were included in our analyses. Birth weight and gestational age data were collected from a state birth registry, medical records, and parent report. Generalized Estimating Equations tested for main effects and interactions between individual SNPs and birth weight centile in predicting ADHD symptom severity. SNPs within neurotrophic (NTRK3) and cytokine genes (CNTFR) were associated with ADHD inattentive symptom severity. There was no main effect of birth weight centile on ADHD symptom severity. SNPs within angiogenic (NRP1 & NRP2), neurotrophic (NTRK1 & NTRK3), cytokine (IL16 & S100B), and kynurenine (CCBL1 & CCBL2) genes moderate the association between birth weight centile and ADHD symptom severity. The SNP main effects and SNP × birth weight centile interactions remained significant after adjusting for multiple testing. Genetic variability in angiogenic, neurotrophic, and inflammatory systems may moderate the association between restricted prenatal growth, a proxy for an adverse prenatal environment, and risk to develop ADHD. © 2014 Wiley Periodicals, Inc.